POTENSI AKTIVITAS ANTIINFLAMASI DAN ANTIKANKER DARI EKSTRAK DAN FRAKSI DAUN ALPUKAT DAN DAUN PEPAYA: NARRATIVE REVIEW - Rahayu, Ihsanti Dwi; Aliya, Fariha Ais; Al Hanif, Jazaul Fariha (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2025)
Avocado leaves and papaya leaves have been empirically widely used by Indonesian people as traditional medicine with various benefits. The discovery and development of new drugs that lead to the use of medicinal plants have triggered the need for accurate and reliable information, especially related to avocado leaves and papaya leaves in the treatment of cancer and inflammation. The purpose of writing this article is to determine the potential of avocado leaves and papaya leaves, both in the form of extracts and fractions, for anti-inflammatory and anticancer activities collected in narrative review articles. The search for articles as reference materials for writing was carried out by combining keywords and boolean operators (AND, OR) typed on article database sites such as Google Scholar, PubMed, and Researchgate. There are inclusion criteria in the search for articles, namely relevant articles in journals that have been published in 2015 to 2024, articles available in full-text in Indonesian or English, and obtained from experimental study research designs. Based on the results of the journal article selection, 23 journal articles were obtained that met the inclusion criteria for the review process. The results of the review of 23 articles show that avocado leaves and papaya leaves have been scientifically proven to have pharmacological activity as anti-inflammatory and anticancer both in the form of extracts and fractions. The content of secondary metabolite compounds that are suspected to be responsible for the production of anti-inflammatory and anticancer activities in avocado leaves and papaya leaves are flavonoid compounds.